Hubungan Empathy Terhadap Friendship Quality Pada Remaja Di Komunitas Generasi Cendekia Sumatera Selatan - Ningsih, Suci Cahya; Noviza, Neni; Fitri, Hartika Utami (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This research is entitled The Relationship between Empathy and Friendship Quality in Adolescents in the South Sumatra Scholar Generation Community, where this research aims to determine the description of the level of empathy, the description of the level of friendship quality, and whether or not there is a relationship between empathy and friendship quality in adolescents in the South Sumatra Scholar Generation Community. This research method uses quantitative descriptive, with a saturated sample. The data collection technique used was through a questionnaire. The data analysis technique used is correlational to determine whether there is a relationship or not. The results obtained from research conducted on empathy among teenagers in the South Sumatra Scholar Generation Community are in the medium category with a percentage of 54.55%, Friendship quality among teenagers in the South Sumatra Scholar Generation Community is in the medium category at 69.70%, and it is known that there is a relationship between empathy and friendship quality among teenagers in the South Sumatra Scholar Generation Community. Keywords: Empathy, Friendship Quality